Strategic Leadership Practices and Devolved Administrative Structures in Selected Semi-Arid Counties in Kenya - Jumanne, Andrew; Njoroge , Dr. Jane; Jemutai , Dr. Edna (American Journal of Leadership and Governance, 2023)
Purpose: The presence of devolved administrative structures plays a critical role in safeguarding against the abuse of power and promoting political stability. Consequently, ensuring the effective operation of these structures in Kenya, especially given the introduction of devolution, is of paramount importance. The primary reason for the existing inadequacies in service delivery has been the suboptimal implementation of these devolved administrative entities, often stemming from ineffective managerial practices. To bridge this gap, this study had four specific objectives aimed at delineating the scope of strategic leadership practices within these devolved administrative structures: assessing the impact of resource allocation practices, evaluating the influence of public accountability practices, scrutinizing the effect of stakeholder involvement, and examining the moderating impact of legal factors on the relationship between strategic leadership practices and these administrative structures. The study incorporated three theoretical frameworks: the resource-based view theory, the transformational leadership theory and the institutional theory. Methodology: The study's target population encompassed 500 participants from Taveta and Makueni counties. Employing purposive and stratified random sampling techniques, a sample size of 223 was derived from the target population. The research design adopted was descriptive research, intended to provide insights into questions regarding what, where, and when. Quantitative and qualitative analytical methods were applied, with SPSS for data coding and STATA version 12 for analysis. Multiple linear regression analysis was conducted to examine the collective impacts of resource allocation practices, public accountability practices, and stakeholder involvement practices on devolved administrative structures. Findings: The study ascertained that strategic leadership practices have the potential to enhance the efficiency of decentralized administrative organizations and streamline the dissemination of information. Recommendations: The research recommends that county leaders articulate plans in a manner that encourages the development of devolved administrative structures, leading to sustainable transformation.